Ideologija in umetnost - Erjavec, Aleš (Vestnik Inštituta za marksistične študije, 1988)
In the article the author points to some basic thesis of his book Ideology and Art of Modernism (Ljubljana, 1988) and adds a few additional remarks. The author sketches the essential conceptualizations of ideology throughout history and states that especially modernist art was fundamentally tied to ideology, especially the political one. As an extreme case of the relationship between ideology and art is taken the totalitarian ideology and its relationship towards art. At the same time its demand for "realistic" art is explained with the help of Pierre Bourdieu's interpretation of representational art as populist art. As two extreme cases of politization of art the period of around First World War and the period of the neoavant-gardes is given. In author's opinion the postmodernist art already transcends the context of modernism and also the relationship of ideology and art as they were typical for modernism of the last century.
Keywords: filozofija; philosophy; ideologija; ideology; umetnost; art